METHODOLOGY OF DEVELOPMENT OF COMPETENCE OF FUTURE PEDAGOGUES IN THE USE OF DIGITAL TECHNOLOGIES - Zohidova Makhfuza Khabibovna (Galaxy International Interdisciplinary Research Journal, 2024)
The integration of digital technologies into education has changed the landscape of teaching and learning and has necessitated the upgrading of educators’ skills in the effective use of these tools. This article presents a comprehensive methodology for developing future educators’ digital technology competence. The methodology includes a holistic approach that combines theoretical foundations, practical training and continuous professional development. The proposed methodology is aimed at equipping future pedagogues with the necessary knowledge, skills and attitudes for effective use of digital technologies in educational institutions.